RANCANG BANGUN ALAT UJI TORSI TIPE PRONY BRAKE UNTUK UNJUK KERJA MESIN MOTOR BAKAR KAPASITAS 6,6 KW - Muh. Irbabunnuha A; Yudhi M Sholihin; M. Dwi Trisno (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2020)
As the need for engines in human life increases, so it also increases the need for fuel used. Therefore, many research about the use of alternative fuels instead of oil fuel. On the motor combustion performance, to know the motor power must be known first its torque. In principle, the dynamometer works by giving the load to the motor rotation which occurs through the braking mechanism on its axis. The price of torque test equipment on the market is high enough so that be a problem for research institutes or small scale workshops who want to test the performance of motor combustion engines. The purpose of this research is to design, build, and test the performance and validate statistically dynamometer that has been designed to have function, accuracy and good validation, simple design, easy operation, and affordable prices. In this research, the dynamometer that designed is a Prony Brake type dynamometer that designed with the VDI 2221 design method. Torsi test equipment or dynamometer that designed with a simple design, easy operation, and an affordable prices. After this dynamometer has been designed and assembled, furthermore this equipment is tested functionally using a General GX270 T2 Honda engine powered by 3kg LPG gas. After conduct the function test, the observational data is validated with statistical standards. From the result of this research obtained valid numbers so that torsi test or dynamometer in this research can be applied in research institutions / small workshop